Understanding Islamic education for pre-school children in Malaysia - Mokhtar Mohed, Mursyidah; Ismail, Nor Atiah; Nangkula, Utaberta; Mohd Yunos, Mohd Yazid; Ismail, Sumarni; Ariffin, Noor Fazamimah (American-Eurasian Network for Scientific Information Publications(AENSI), 2015)
Islam is not a belief but a way of life for Muslims. When a child is young, they can easily absorb knowledge when taught to, so instilling Islamic teachings among pre-school children should be easy at this age. The current problem with Islamic education in Malaysia though is that the society themselves, especially Muslims, do not give emphasis on Islamic subject. Objectives: To find out the current general and Islamic Education guidelines for Pre-School in Malaysia and public preschools differ with private preschools. Results: Islamic education should be taught at least two hours in one week, according to the current syllabus and private preschools put much more emphasis on Islamic education compare to public preschool. Conclusion: Islamic education is an important aspect in pre-school learning and it should be made compulsory in the current syllabus by using the current guidelines provided.